Frequency of pre-eruptive intracoronal resorption in panoramic radiographs of peruvians: a cross-sectional study - Pérez Lip, Iván Eduardo (2024)
Objective: To determine the frequency of Preeruptive Intracoronal Resorption (PIR) in a sample of digital panoramic radiographs of Peruvian patients between 3 to 21 years of age who attended an oral and maxillofacial radiology center between 2013 and 2021. Material and Methods: This observational study was descriptive, retrospective and cross-sectional. A sample of 1897 digital panoramic radiographs were evaluated to determine the frequency of PIR and its covariates of location, depth, and inclination of the affected teeth. The authors’ calibration was performed before the study. The intraoperator agreement was determined by calculating the Kappa coefficient (0.72, CI 0.67-0.76). The radiographs were evaluated by the study's principal author (IEP), and the data were collected in a form designed for the study. The statistical association was determined using the Chi-square test, with a confidence level of 95%, and a p-value of less than 0.05 was considered significant. Results: The frequency of PIR was 3.95%, with no statistically significant difference between sexes (p>0.05). The most common findings were PIR in the lower right second molar (32.5%), a singular defect (89.3%), central location (44.5%), and superficial dentinal involvement (83.1%). These results aligned with existing literature. Conclusions: Our results describe the epidemiological profile of PIR in the present sample as a single radiolucent and small (grade I) defect located centrally in the coronal dentin, often affecting posterior lower teeth with a frequency lesser than 5%. These findings provided valuable insights for clinicians and researchers regarding the frequency and characteristics of PIR in Peruvian patients.